2020
DOI: 10.1080/15412555.2019.1707789
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of WatchPAT for the Diagnosis of Obstructive Sleep Apnea in Patients with Chronic Obstructive Pulmonary Disease

Abstract: The coexistence of chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA), termed the overlap syndrome (OVS), is associated with adverse outcomes that may be reversed with treatment. However, diagnosis is limited by the apparent need for in-laboratory polysomnography (PSG). WatchPAT is a portable diagnostic device that is validated for the diagnosis of OSA that might represent an attractive tool for the diagnosis of OVS. Subjects with established COPD were recruited from a general popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…Several prior studies evaluated the reliability of WatchPat testing, showing strong correlations between AHI and pAHI, in the range of 0.85-0.90. [13][14][15][16][17][18][19][20][21][22][23] First, although the overall correlation coefficient and markers of central tendency such as mean bias and its 95% CI are important, some of the previous publications did not explore or present in detail the high dispersion of the residuals and their practical implications. Second, when evaluating a new device or method of testing, what is of significance to the clinician is not the combination of sensitivity and specificity, but rather the positive and negative predictive values.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies evaluated the reliability of WatchPat testing, showing strong correlations between AHI and pAHI, in the range of 0.85-0.90. [13][14][15][16][17][18][19][20][21][22][23] First, although the overall correlation coefficient and markers of central tendency such as mean bias and its 95% CI are important, some of the previous publications did not explore or present in detail the high dispersion of the residuals and their practical implications. Second, when evaluating a new device or method of testing, what is of significance to the clinician is not the combination of sensitivity and specificity, but rather the positive and negative predictive values.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies had evaluated the reliability of WatchPat 200 testing, showing correlations up to 0.90 between PSG AHI and PAT-based AHI (pAHI), while the practical implications of the large dispersion had been occasionally ignored or deemed negligible. [17][18][19][20][21][22][23][24][25][26][27] Recently, in a point-of-care investigation, we have shown that automatically scored WatchPat 200 tests could lead to significant misclassification rates (30%-50%) in the diagnosis of OSA and its severity against 'gold standard' PSG. 6 In these new analyses of the same 500 participants evaluated with synchronous PSG and PAT-based HSAT devices, we found that the WatchPat 200-derived ODI 4% and Hypoxic burden, in concert with various demographic (age, gender) or anthropometric (BMI, NC) data, can improve the diagnostic accuracy and severity classification of this disease up to 85%-86%.…”
Section: Discussionmentioning
confidence: 99%
“…Portable and home sleep apnea testing (HSAT) may have adequate sensitivity to diagnose OSA in COPD 59,60 . However, current guidelines recommend against use of HSAT in patients with significant chronic respiratory disease due to the following shortcomings 61 .…”
Section: Diagnosis Of Overlap Syndromementioning
confidence: 99%